PUSAT OLAHRAGA UNTUK DIFABEL BANJARBARU - Firdaus, Muhammad; Hartono, Rudi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Sports Center for Diffable is a facility for people with special needs (diffable) in improving sports performance. Sports center for people with disabilities also represents an answer to the issues for people with special needs for their rights in livelihood and life including in terms of sport. The architectural problem raised in this report is how to design a Sports Center that can fulfill the building size and capacity of the National standard (Type A) for a competition, by paying attention to the accessibility of the building. The accessibility design is used as the main concept to solve the problem of the Sports Center for people with disabilities. Accessibility is the convenience provided for everyone to manifest an equal opportunity in every aspect of life especially the facilities that cover all activities related to sport for people with special needs.